Antiproliferative, Apoptotic, and Autophagic Activity of Ranibizumab, Bevacizumab, Pegaptanib, and Aflibercept on Fibroblasts: Implication for Choroidal Neovascularization - Lyubomyr Lytvynchuk; Andrii Sergienko; Galina Lavrenchuk; Goran Petrovski (Journal of Ophthalmology)
Purpose. Choroidal neovascularization (CNV) is one of the most common complications of retinal diseases accompanied by elevated secretion of vascular endothelial growth factor (VEGF). Intravitreal anti-VEGFs (ranibizumab, bevacizumab, pegaptanib, and aflibercept) can suppress neovascularization, decrease vascular permeability and CNV size, and, thereby, improve visual function. The antiproliferative, apoptotic, and autophagic effect of anti-VEGF drugs on fibroblasts found in CNVs has not been yet explored. Methods. Concentration-dependent cellular effects of the four anti-VEGFs were examined in L929 fibroblasts over a 5-day period. The cell survival, mitotic and polykaryocytic indices, the level of apoptosis and autophagy, and the cellular growth kinetics were all assessed. Results. The anti-VEGFs could inhibit the survival, mitotic activity, and proliferation as well as increase the cellular heterogeneity, apoptosis, and autophagy of the fibroblasts in a dose-dependent manner. Cellular growth kinetics showed ranibizumab to be less aggressive, but three other anti-VEGFs showed higher antiproliferative and apoptotic activity and expressed negative cellular growth kinetics. Conclusions. The antiproliferative, apoptotic, and autophagic activity of anti-VEGFs upon fibroblasts may explain the cellular response and the etiology of CNV involution in vivo and serve as a good study model for CNV in vitro.